EARLY DIAGNOSIS AND PATHOGENESIS OF HEART FAILURE IN PATIENTS WITH REFRACTORY HYPERTENSION AND DISORDERS OF CARBOHYDRATE METABOLISM - A. V. Safronenko; Y. S. Maklyakov; N. V. Sukhorukova; A. V. Krishtopa (Медицинский вестник Юга России, 2013)
Purpose: To reveal the peculiarities of violations of the vegetative regulation of a rhythm of cardiac activity in patients with refractory hypertension on the background of type 2 diabetes.Materials and methods: we examined 30 patients with hypertension (group 1) and 16 patients with refractory hypertension(group 2). Patients of the two groups were of type 2 diabetes. Control group - 30 practically healthy people. All patients were Holter ECG monitoring, autonomic tests Шелонга, Вальсальвы, the sample with a deep breath, and also evaluated the oxidative modification of proteins and antioxidant protection.Results: in 1-St and 2-nd groups identified the reduction of pNN50 to 20.2± 2.9 ms and 10.4± 4.1 ms and rMSSD to 31.2± 5.3% and 23.9± 6.1%,respectively. Electrical instability infarction is detected in 60% of patients of the 1st group and in 81.2% of patients of the 2nd group in the form of альтернации detection.Summary: the violation of the variability of cardiac rhythm - earlier manifestation of defeat infarction in patients with hypertension and diabetes 2типа, and a progressive decline in the activity of the parasympathetic nerve and/or the increase of the sympathetic Department of the vegetative nervous system is associated with increased intensity of oxidative modification of proteins.